Entry and Ramifications of Neo-Liberalism for Education in Tanzania: What is the Possible Alternative? - Kahangwa, George (Papers in Education and Development, 2018)
What takes place in an education system is influenced by, among other things, ideologies that exist in society. In recent years, the ideological influence on education in Tanzania has changed from Ujamaa thinking to neo-liberalism. This paper traces the entry of the latter into Tanzania ' s education and its ramifications. The paper is based on a study whose objectives were to establish how neo-liberalist ideas entered Tanzania ' s education system; identify the ramifications and impact of neo-liberalism on the provision of education in Tanzania; and trace the possible ideological alternative for Tanzania ' s education. It is argued in the paper that neo-liberalism has been responsible for the introduction of problematic cost-sharing policies in education, the under-financing of education, and attenuation of education quality. On a wider scope, ideology has also caused the failure of locally produced goods, the market for agricultural products to diminish, agricultural crop prices to plummet, the number of youth petty traders to increase in urban centres, and many to lose their jobs. Since Tanzania needs to address the negative impact of neo-liberalism, the paper proposes what could be a suitable alternative ideology for education in the country. Key words: Neo-liberalism, Education, Tanzania